answersLogoWhite

0


Best Answer

It can be simplified to: 2x+33

User Avatar

Wiki User

โˆ™ 2013-07-08 09:32:08
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is the answer for 3 plus 2x plus 30?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is x2 plus 2x plus 15 divided by x-3?

(x2 + 2x + 15)/(x - 3) = x + 5 + 30/(x - 3) where x ≠ 3


How do you solve 4x plus 3 equals -3 plus 2x plus 14?

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4


What is the answer for 2x plus 3 plus 23x?

2x + 3 + 23x = 25x +3


7 plus 7x--2x plus 3?

2x + 3=7x


What is 4x plus 3 plus 2x?

4x plus 3 plus 2x is equivalent to expression 6x plus 3.


What is (2x plus 3) (x plus 1)?

(2x + 3)(x + 1 ) = 2x^2 +5x +3


What is 3 plus 3 plus 2x?

3 + 3 + 2x = 0 6 + 2x = 0 2x = -6 x = -6/2 x = -3


How do you simplify 2x plus 4x plus 3?

2x + 4x + 3 = 6x + 3


What is the simplification form of 2x plus 3-10?

Simplist form of 2x plus 3-10 is 2x-7.


What are the factors of 2x squared plus 9x plus 9?

(2x+3)(x+3)


Y equals xsquared plus 2x-3?

-1


What is the multiplicitive inverse of 3 plus 2x?

The multiplicative inverse of 3+2x is 1/(3+2x).


What is 2x plus 2x plus 2x?

6x with 3 over the x, because that is how many x's there are.


What is the answer to 2x equals X plus 3?

2x = x+3 2x-x = 3 x = 3


How do you solve 7x plus 3y equals 30 -2x plus 3y equals 3 in an order pair?

(3,3)


How do you factor 2x to the second power plus 5x plus 3?

(2x + 3)(x + 1)


How do you factor 4x2 plus 12x plus 9 equals 0?

(2x + 3)(2x + 3)


What is 5x - 3 plus 2x plus 7?

5x - 3 + 2x + 7 = ?7x + 5 = ?


What is 2x plus 5x plus 3?

7x + 3


Factor the polynomial expression 6x2 plus 11x plus 3?

6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)


What is 8x cubed plus 4x squared plus 6x plus 3?

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)


What is 2x plus 3 equals 9?

if 2x+3=9 then 2x=6 so x=3


What is x when 2x equals 4x plus 3?

2x = 4x + 3 -2x = 3 x = -3 / 2


Simplify x - 2x plus 3?

x - 2x + 3 = 3 - x


Factor 8x cubed plus 2x squared plus 12x plus 3?

The answer is (2x^2+3)(4x+1)